Preliminary evaluation of turmeric (Curcuma longa L.) varieties at Konkan region of Maharashtra - S A Ranpise, G D Joshi, B B Mahale, P V Sinkar, P M Haldankar, R G Khandekar (Journal of Spices and Aromatic Crops, 2005)
The performance of 21 varieties of turmeric (Curcuma longa) for rhizome characters, yield and curcumin content was studied at Konkan region (Maharashtra). Salem was found to be the best variety, which recorded significantly higher weight of primary fingers (208.92 g), secondary fingers (243.75 g), yield plot’ (11.99 kg) and yield hectare" (44,395 kg). The curcumin content was significantly higher in CA-71 (4.87%). The phenotypic and genotypic coefficient of variation, heritability and genetic advance on mean basis were appreciably high for yield and curcumin content. The magnitude for environmental coefficient of variation was very low.